Integrating Concept of Entrepreneurship Into Science Education - Muhammad Muhammad (Universitas Muhammadiyah Mataram, 2018)
Science learning should become meaningful and useful experience for the students to answer problems in daily life, especially economical problems. Through the integration of science learning and entrepreneurship it is hoped that entrepreneur character develops in the children’s self. The main components of entrepreneurship consist of three aspects, namely creative force, sense, and intention. Creative force creates the characters of innovative, creative, careful, organized, broadening insight, problem solver, and reflective. Sense aspect creates the characters of confident, want to gain profit, able to serve, truthful, determined, optimistic, and sharp to chances. Intention creates the character of brave, risk taking, hard work, cooperative, responsible, listening to inputs, able to negotiate, discipline, and dynamic. Science learning integrated with entrepreneurship is required to develop learning activities yielding comprehensive meaning and benefit.